2003
DOI: 10.3122/jabfm.16.1.14
|View full text |Cite
|
Sign up to set email alerts
|

Underdiagnosis of Obesity at a Community Health Center

Abstract: Background: Obesity is at epidemic proportions. This study examined the extent to which obesity is being diagnosed at a community health center residency-training site. Results were examined by provider type. Characteristics of patients with obesity diagnosed by primary care providers were compared with characteristics of patients determined to be obese by body mass index (BMI) calculation exclusively.Methods: A cross-sectional design was used. Medical records of 465 adult patients were audited. Data collected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 28 publications
1
38
0
Order By: Relevance
“…[8][9][10] Physicians also have been found to misperceive their own weight status and that of their patients, 11,12 and to infrequently use BMI measurements in their practices. 13,14 Although the US Surgeon General has issued a 'call to action,' and the lay press and professional literatures are replete with articles discussing the health risks associated with obesity, these warnings may miss their intended targets if affected individuals fail to recognize the personal relevance of the warnings or health-care providers fail to appropriately identify and counsel the overweight patients they treat. 15,16 Assessing perceptions of the terms 'overweight' and 'obese' has been approached through a variety of methods.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] Physicians also have been found to misperceive their own weight status and that of their patients, 11,12 and to infrequently use BMI measurements in their practices. 13,14 Although the US Surgeon General has issued a 'call to action,' and the lay press and professional literatures are replete with articles discussing the health risks associated with obesity, these warnings may miss their intended targets if affected individuals fail to recognize the personal relevance of the warnings or health-care providers fail to appropriately identify and counsel the overweight patients they treat. 15,16 Assessing perceptions of the terms 'overweight' and 'obese' has been approached through a variety of methods.…”
Section: Introductionmentioning
confidence: 99%
“…13 In a national study of 12,835 adults classified as obese, only 42% reported that their health care provider advised them to lose weight. 14 The purpose of this study was to determine the extent that primary care providers assess overweight and obesity and document treatment strategies in a family medicine setting during well visits. Review of medical records provided data to assess the use of BMI for adults and BMI-for-age for children and allowed examination of the documentation of patient education concerning body weight, diet, and exercise.…”
mentioning
confidence: 99%
“…Our overall results are similar to those from the Connecticut Cancer Registry, also a participant in the SEER program, which found 79% of a random sample (n=618) of invasive cancer patients to have height and weight recorded in hospital admissions records at cancer diagnosis (19). To our knowledge, no other studies have assessed the availability of this information in the medical records of cancer patients, however, in a study of non-cancer patients, 63% of adults (n=465) scheduled to receive care at a community health center over a one-week period had height, at any time, and weight, within the prior 6 months, recorded in the medical record (24).…”
Section: Discussionmentioning
confidence: 99%